ANNEXIN A1: Roles in Placenta, Cell Survival, and Nucleus - de Sousa, Stefanie Oliveira [UNESP]; Dos Santos, Mayk Ricardo [UNESP]; Teixeira, Samuel Cota; Ferro, Eloisa Amália Vieira; Oliani, Sonia Maria [UNESP] (MDPI, 2022)
The unbiased approaches of the last decade have enabled the collection of new data on the biology of annexin A1 (ANXA1) in a variety of scientific aspects, creating opportunities for new biomarkers and/or therapeutic purposes. ANXA1 is found in the plasma membrane, cytoplasm, and nucleus, being described at low levels in the nuclear and cytoplasmic compartments of placental cells related to gestational diabetic diseases, and its translocation from the cytoplasm to the nucleus has been associated with a response to DNA damage. The approaches presented here open pathways for reflection upon, and intrinsic clarification of, the modulating action of this protein in the response to genetic material damage, as well as its level of expression and cellular localization. The objective of this study is to arouse interest, with an emphasis on the mechanisms of nuclear translocation of ANXA1, which remain underexplored and may be beneficial in new inflammatory therapies.
Keywords: gestational diabetes mellitus; human placenta; inflammation; nuclear translocation; peptide Ac2-26